Romantic Ideas in William Wordsworth’s Play The Borderers - Rany Syafrina (STBA Prayoga Padang, 2017)
William Wordsworth is mostly known as a poet, but in reality he also wrote a closet drama The Borderers. As an author, William Wordsworth is also influenced by his surrounding society, political movement, as well as philosophical ideas of Romanticism. As the result, most of his works contain the aspect of Romanticismsin the use of language as well as in developing the story. This research, tries to describe the Romantic aspects in William Wordsworth The Borderer, includingthe celebration of the nature, the importance of dream, and an interest toward social surrounding. In writing his work, Wordsworth not only describes thelandscape as it is, but he also adds his personal experience in exploring the countryside as well as in presenting his social critique. Wordsworth uses bothlandscape and dreams to criticize the society and to describe the possibility of good and bad in human nature. In consequence, The Borderers is not onlyconsidered as a common play but also a private writing about Wordsworth disappointment toward his social surrounding.